Implementasi Media Wordwall dalam Meningkatkan Minat Belajar Siswa pada Mata Pelajaran SKI di SMA Jati Agung, Wage, Taman, Sidoarjo - Firnanda, Noorma Dewi; Yuliastutik, Yuliastutik; Marfiyanto, Tri (YASIN, 2025)
Implementation of Wordwall Media in increasing students' interest in learning at Jati Agung High School, Wage, Taman, Sidoarjo. This research aims to explore the role of wordwall learning media in increasing students' interest in learning at the high school level. This research uses a qualitative approach with narrative descriptive as the main method. The data collected in this research went through various stages such as classroom observations, in-depth interviews with teachers and several students, as well as analysis of related documents needed in the research. The research results show that the implementation of various and varied Wordwall learning media can help students' learning process and is significant in increasing students' interest in learning. Students show a positive response to the use of technology in this media in the teaching and learning process which can provide a better understanding of concepts and increase student involvement to become more active in the learning process. The implementation of wordwall media in increasing students' interest in learning is in accordance with the theory of planned behavior which believes in the existence of factors that can support behavior and awareness of the strength of these factors such as learning objectives, student characteristics, learning materials, facilities and learning media. From several factors, the author took one of them, namely wordwall learning media. The theory of planned behavior states that a person is said to have learned if there is a change in behavior in delivering material that has been given by the teacher and students provide stimulus in the form of a response. With the presence of wordwall media, students show changes in behavior in the form of enthusiasm for learning. These findings show the importance of appropriate learning media in education to stimulate students' interest in learning effectively. This research suggests the need for improvement in the development of learning media that is interesting and meaningful for teachers and students.